Highly processable soft acrylic resin
A multi-stage flexible acrylic resin with a branched polymer structure addresses the processing challenges of existing acrylic resins by reducing viscosity and improving tensile properties, enabling the production of transparent, thin films suitable for extrusion and injection molding.
Patent Information
- Application Number
- JP2021557592
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-28
- Filing Date
- 2020-03-13
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-03-13
AI Technical Summary
Existing acrylic resins are either too expensive, too hard, or have low tear resistance, and their high viscosity makes them difficult to process into thin films or certain injection molding applications, while alternative polymers like polyvinyl chloride or polyethylene may not meet performance requirements and can have environmental drawbacks.
A multi-stage flexible acrylic resin composition with a branched polymer structure, comprising a crosslinkable core and intermediate layers with specific monomer compositions and controlled crosslinking, reduces viscosity without causing flute whitening, and improves tensile properties and processing window.
The composition achieves lower viscosity for easier processing, improved tensile properties, and wider processing windows, enabling the production of transparent, thin films without flute whitening, suitable for extrusion and injection molding.
Smart Images

Figure 0007617849000001 
Figure 0007617849000002 
Figure 0007617849000003
Abstract
Description
[Technical field]
[0001] The field of the invention is flexible acrylic resin compositions and films made from such compositions. Summary of the Invention [Problem to be solved by the invention]
[0002] A variety of indoor and outdoor products benefit from the use of flexible, clear, weather-resistant plastic materials. Fluorine-containing polymers and thermoplastic polyurethanes offer these characteristics but are too expensive for many end uses. Low-cost resins, such as polyvinyl chloride or polyethylene resins with plasticizers, may not meet all performance requirements. Some of these polymers may have undesirable environmental impacts.
[0003] Various acrylic resins have also been proposed. However, many are too hard, have a high modulus, or have low tear resistance for certain end uses. One commercially available acrylic resin contains a block copolymer of poly(methyl methacrylate) and poly(butyl acrylate) produced by anionic polymerization. These resins are flexible and resistant to whitening, but are prohibitively expensive for certain applications. Multi-stage acrylic polymers have been taught as an alternative (see, for example, U.S. Pat. No. 10,040,915). These materials tend to be highly viscous (melt flow index or rate in the range of 10 g / 10 min at 220° C. and 10 kg) and difficult to process for certain applications.
[0004] Disclosed herein is a composition comprising a multi-stage flexible acrylic resin and a branched polymer that is the reaction product of reactants including one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1-10 weight percent, and a crosslinker in an amount of 0.1-10 weight percent of the crosslinker, the weight percent being based on the total amount of reactants, with the proviso that the amount of crosslinker in molar does not exceed the amount of chain transfer agent in molar. The branched polymer is not crosslinked.
[0005] Also disclosed herein is an extruded film comprising a layer of the above composition, which layer is 150 microns or less, is transparent, and does not exhibit crease whitening. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] Disclosed herein is a composition comprising a multi-stage soft acrylic resin and a branched polymer. The inventors have found that the viscosity of the multi-stage soft acrylic resin is too high to allow the resin to be used in certain applications, such as when it is desired to extrude very thin films or in certain injection molding applications. Increasing the processing temperature can degrade the resin. Although the addition of a low molecular weight linear additive can reduce the viscosity (increase the melt flow index), the inventors have found that the resulting product in some cases exhibits fluting whitening, which may indicate phase separation of the mixture. Surprisingly, the inventors have found that the disclosed branched polymer reduces the viscosity without exhibiting undesirable fluting whitening. In addition, the composition with the branched polymer additive can exhibit improved tensile properties and a wider processing window compared to a similar composition with a linear additive.
[0007] According to certain embodiments, the multi-stage flexible acrylic resin comprises a multi-stage sequential polymer composition including a first stage crosslinked acrylic polymer composition forming a core, one or more intermediate layer acrylic polymer compositions, and an outer layer acrylic polymer composition, the core and the intermediate layer(s) and outer layer differ in one or more of the following: derived from different acrylate monomers, degree of crosslinking (intermediate and outer layers may or may not be crosslinked), and glass transition temperature. The acrylic polymer composition is formed from a reaction mixture including one or more hydrocarbyl acrylates or hydrocarbyl methacrylates, optional crosslinking agents (except some crosslinking agents are required for the core), and optional chain transfer agents. According to certain embodiments, the multi-stage flexible acrylic resin comprises a first stage that is the reaction product of one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates with one or more crosslinking monomers, graft linking monomers, or combinations thereof. According to certain embodiments, the amount of units derived from alkyl acrylate and / or alkyl methacrylate monomers ranges from 95 to 99.9 weight percent of the first stage, and the amount of units derived from crosslinking and / or graft-linking monomers ranges from 0.1 to 5 weight percent. According to certain embodiments, this first stage is crosslinked with a Tg in the range of -85 to -10°C. The first stage may also be referred to as the core. The resin comprises one or more intermediate stage layers, each of which comprises 93 to 100 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates, 0 to 5 weight percent of units derived from crosslinking monomers, graft-linking monomers, or combinations thereof, and optionally 0 to 2.0 weight percent of units derived from one or more chain transfer agents, with a compositional gradient between the intermediate layers such that the Tg transitions from -30°C to 70°C across the width of the intermediate region.The resin further comprises an outer stage or outermost layer comprising 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, and styrenic monomers, and combinations thereof, 0 to 1.5 weight percent units derived from one or more chain transfer agents, and has a Tg of 40°C to 110°C.
[0008] The crosslinkable core comprises greater than 95 to 99.9 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylate or alkyl methacrylate monomers. All individual values and subranges from 95 to 99.9 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be from a lower limit of 95, 95.5, 96, 96.5, 97, 975, 98, 98.5, 99, or 99.5 weight percent to an upper limit of 95.3, 95.8, 96.3, 96.9, 97.5, 98, 98.7, 99.4, or 99.9 weight percent. For example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 95 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 95 to 97.5 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 97.8 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 96.5 to 97.9 weight percent.
[0009] The crosslinkable core comprises 0.1 to 5 weight percent units derived from crosslinking monomers, graftlinking monomers, or combinations thereof, all individual values and subranges from 0.1 to 5 weight percent are included herein and disclosed herein, for example, the amount of units derived from crosslinking monomers, graftlinking monomers, or combinations thereof can be from a lower limit of 0.1, 0.7, 1.2, 1.9, 2.6, 3.1, 3.7, 4.4, or 4.9 weight percent to an upper limit of 0.2, 0.8, 1.4, 2.1, 2.7, 3.3, 3.8, 4.5, or 5 weight percent. For example, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.1 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.5 to 2.5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 1.0 to 4.0 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.3 to 3.5 weight percent.
[0010] The crosslinkable core has a Tg of -85 to -10° C. All individual values and subranges of -70 to -10° C. are included herein and disclosed herein, for example, the Tg of the crosslinkable core can be from a lower limit of -85, -80-70, -60, -50, -40, -30, -20, or -15° C. to an upper limit of -75, -65, -55, -45, -35, -25, -17, or -10° C. For example, the Tg of the crosslinkable core can be in the range of -85 to -10° C., or alternatively, the Tg of the crosslinkable core can be in the range of -60 to -40° C., or alternatively, the Tg of the crosslinkable core can be in the range of -70 to -50° C., or alternatively, the Tg of the crosslinkable core can be in the range of -50 to -30° C.
[0011] The intermediate region includes one or more intermediate layers. All individual values and subranges of the one or more intermediate layers are disclosed and included herein. For example, the intermediate region can include one, two, three, four, or five intermediate layers.
[0012] Each of the intermediate layers comprises up to 100 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylate or alkyl methacrylate monomers. All individual values and subranges up to 100 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more alkyl (meth)acrylate monomers can be from the lower limit of 88.5, 89.4, 90.7, 91.8, 92.6, 93.7, 94, 94.9, 95.5, 96, 97.4, 98.1, 99.3, 99.9, or 100 weight percent. For example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 88.5 to 100 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 90.5 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 88.5 to 94.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers may range from 92.5 to 96 weight percent.
[0013] Each of the intermediate layers comprises 0 to 5 weight percent of units derived from a crosslinking monomer, a graftlinking monomer, or a combination of two or more thereof, all of the individual values and subranges are included herein and disclosed herein, for example, the amount of units derived from a crosslinking monomer, a graftlinking monomer, or a combination thereof can be from a lower limit of 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 4.5 weight percent, to an upper limit of 0.2, 0.7, 1.2, 1.7, 2.5, 2.7, 3.2, 3.7, 4.2, 4.7, or 5 weight percent. For example, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 0 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 0 to 2.5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 2.5 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 2 to 4 weight percent.
[0014] Each of the intermediate layers optionally comprises 0 to 2.0 weight percent units derived from one or more chain transfer agents, all individual values and subranges from 0 to 2.0 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more chain transfer agents can be from a lower limit of 0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, or 2.0 weight percent to an upper limit of 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.7, or 1.9 weight percent. For example, the amount of units derived from the one or more chain transfer agents can be in the range of 0 to 2.0 weight percent, or, alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0.75 to 2.0 weight percent, or, alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0 to 0.75 weight percent, or, alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0.5 to 1.0 weight percent.
[0015] Between the intermediate layers there is a compositional gradient such that the Tg transitions across the width of the intermediate region from -30° C. to 70° C. All individual values and subranges from -30° C. to 70° C. are included herein and disclosed herein, for example, the Tg transitions from a lower limit of -30, -20, -10, 0, 10, 20, 30, 40, 50, or 60° C. to an upper limit of -25, -15, -5, 5, 15, 45, or 70° C. For example, the Tg may transition over a range of -30 to 70°C, or alternatively, the Tg may transition over a range of -10 to 30°C, or alternatively, the Tg may transition over a range of -30 to -15°C, or alternatively, the Tg may transition over a range of -25 to 0°C, or alternatively, the Tg may transition over a range of 0 to 15°C, or alternatively, the Tg may transition over a range of -15 to 55°C, or alternatively, the Tg may transition over a range of 5 to 35°C.
[0016] The outermost layer comprises 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof. All individual values and subranges from 98.5 to 100 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof can be from a lower limit of 98.5, 98.7, 98.9, 99.1, 99.3, 99.5, 99.7, or 99.9 weight percent to an upper limit of 98.6, 98.8, 99, 99.2, 99.4, 99.6, 99.8, or 100 weight percent. For example, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof may be in the range of 98.5 to 100 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof may be in the range of 98.5 to 100 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, and .... Alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, styrenic monomers, and combinations of two or more thereof may be in the range of 98.5 to 100 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof may be in the range of 98.5 to 99.6 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, styrenic monomers, and combinations of two or more thereof may be in the range of 96.5 to 100 weight percent.
[0017] The outermost layer comprises 0 to 1.5 weight percent units derived from one or more chain transfer agents. All individual values and subranges from 0 to 1.5 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more chain transfer agents can be from a lower limit of 0, 0.2, 0.4, 0.6, 0.8, 1, 1.2, or 1.4 weight percent to an upper limit of 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, or 1.5 weight percent. For example, the amount of units derived from one or more chain transfer agents can be in the range of 0 to 1.5 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0 to 0.75 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0.75 to 1.5 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0.3 to 1.2 weight percent.
[0018] The outermost layer has a Tg of 40° C. to 110° C. All individual values and subranges from 50° C. to 110° C. are included herein and disclosed herein, for example, the Tg of the outermost layer can be from a lower limit of 40, 43, 45, 50, 60, 70, 80, 90, or 100° C. to an upper limit of 55, 65, 75, 85, 95, 105, or 110° C. For example, the Tg of the outermost layer can be in the range of 40° C. to 110° C., or alternatively, the Tg of the outermost layer can be in the range of 45° C. to 80° C., or alternatively, the Tg of the outermost layer can be in the range of 75° C. to 110° C., or alternatively, the Tg of the outermost layer can be in the range of 65° C. to 95° C.
[0019] In the above case, the Tg of the copolymer can be calculated by the Fox equation [Bulletin of the American Physical Society 1,3 Page 123 (1956)] as follows:
number
[0020] For copolymers, w1 and w2 refer to the weight fractions of the two comonomers based on the weight of monomer charged to the reactor, and T g(1) and T g(2) refers to the glass transition temperatures of the two corresponding homopolymers in degrees Kelvin. For polymers containing three or more monomers, additional terms are added (w n / T g(n) For purposes of this invention, the glass transition temperatures of homopolymers are those reported in "Polymer Handbook," edited by J. Brandrup and EH Immergut, Interscience Publishers, 1966, but if that publication does not report the Tg of a particular homopolymer, the Tg of the homopolymer is measured by differential scanning calorimetry (DSC).
[0021] The alkyl of the alkyl acrylate or alkyl methacrylate can be a linear or branched alkyl group having 1 to 12 carbon atoms. Exemplary monomers include, and exemplary useful alkyl groups include, butyl acrylate, ethylhexyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, and iso-octyl acrylate.
[0022] Examples of crosslinking and / or graft linking monomers useful in the crosslinkable core and intermediate layers may include, for example, butanediol diacrylate, butanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, divinylbenzene, diethylene glycol diacrylate, diethylene glycol dimethacrylate, diallyl maleate, allyl methacrylate, diallyl phthalate, triallyl phthalate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate blends thereof, and combinations of two or more thereof.
[0023] According to certain embodiments, the composition comprises the multi-stage soft acrylic resin in an amount of at least 15, 20, 30, 40, 50, 60, 70, 75, or 80 weight percent, and up to 95 or 90 weight percent, based on the total weight of the composition.
[0024] According to certain embodiments, the soft acrylic resin may be blended with another polymer, examples of which include acrylate or acrylic polymers such as poly(methyl methacrylate), polyesters, polycarbonates, polyamides, and halogenated polyolefins having at least 20 or at least 40 weight percent halogen, such as polyvinyl chloride.
[0025] The branched polymer is a reaction product of reactants including one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1-10 weight percent, and a crosslinker in an amount of 0.1-10 weight percent of the crosslinker, the weight percent being based on the total amount of reactants. The branched polymer is not crosslinked. To avoid crosslinking, the amount of crosslinker does not exceed the amount of chain transfer agent. Thus, according to certain embodiments, the moles of crosslinker are equal to or less than the moles of chain transfer agent. According to certain embodiments, the weight percent of crosslinker is less than the weight percent of chain transfer agent.
[0026] Suitable monoethylenically unsaturated ester monomers useful for making branched polymers according to certain embodiments can have the structure R'-C(O)OR, where R is a hydrocarbyl group (e.g., an alkyl group or an aryl group) and R' is a monoethylenically unsaturated aliphatic group having at least 2 or 3 carbon atoms. According to certain embodiments, R is an alkyl group of at least 1 or 2 or 3 carbon atoms. According to certain embodiments, R is an alkyl group having 12 or 10 or 8 or 6 or 5 or less carbon atoms. According to certain embodiments, R is an aryl group of 6 to 12 carbon atoms. According to certain embodiments, R' has 6 or less carbon atoms. Examples of suitable monomers include butyl acrylate, ethylhexyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, cyclohexyl (meth)acrylate, cyclopentyl methacrylate, tetrahydrofurfyl methacrylate, and benzyl (meth)acrylate. Combinations of two or more such monoethylenically unsaturated ester monomers can be used. For example, a combination of methyl methacrylate and butyl methacrylate can be used. For example, the amount of methyl methacrylate can be at least 20, 30, 40, 50, 60, 70, or 80 weight percent of the reactants, for example, less than 99.8, 99, 98, 97, 96, 95, 90, or 85 weight percent of the reactants. The second monoethylenically unsaturated ester monomer (e.g., butyl acrylate) can be 0 or more than 0, 1, 2, 3, 4, or 5 weight percent of the reactants and less than 60, 50, 40, 30, 20, or 10 weight percent of the reactants. In certain embodiments, additional monoethylenically unsaturated ester monomers can be used. The combination of the second and additional monoethylenically unsaturated monomer(s) together in such embodiments is more than 0, 1, 2, 3, 4, or 5 weight percent of the reactants and less than 60, 50, 40, 30, 20, or 10 weight percent of the reactants.
[0027] According to certain embodiments, one or more additional monounsaturated addition polymerizable (e.g., monoethylenically unsaturated) monomers may be included. For example, styrene or acrylonitrile may be added. The amount of such additional monounsaturated addition polymerizable monomers is preferably less than 10 or 5 weight percent based on the weight of the reactants.
[0028] The reactants further include a chain transfer agent (CTA). The chain transfer agent can be any compound known or found to be useful as a chain transfer agent in the polymerization of acrylate or methacrylate monomers. For example, a thiol chain transfer agent can be used. Examples of such thiol CTAs include monofunctional and multifunctional thiols. Monofunctional thiols include, but are not limited to, propyl mercaptan, butyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecyl mercaptan, thioglycolic acid, mercaptopropionic acid, alkyl thioglycolates, such as 2-ethylhexyl thioglycolate or octyl thioglycolate, mercaptoethanol, mercaptoundecanoic acid, thiolactic acid, and thiobutyric acid. Multifunctional thiols include trifunctional compounds such as trimethylolpropane tris(3-mercaptopropionate), tetrafunctional compounds such as pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetrathioglycolate, pentaerythritol tetrathiolactate, pentaerythritol tetrathiobutyrate, hexafunctional compounds such as dipentaerythritol hexa(3-mercaptopropionate), dipentaerythritol hexathioglycolate, and octafunctional thiols such as tripentaerythritol octa(3-mercaptopropionate), and tripentaerythritol octathioglycolate. The use of multifunctional thiols is a useful method for increasing the branching degree of the polymer. Optionally, the chain transfer agent may include a mixture of two or more compounds. According to one embodiment, the CTA is [ka] It is.
[0029] The alternative chain transfer agent can be any species known to reduce molecular weight in conventional free radical polymerization of vinyl monomers. Examples include sulfides, disulfides, halogen-containing species. Catalytic chain transfer agents such as cobalt complexes, e.g., cobalt(II) chelates such as cobalt porphyrin compounds, are also useful chain transfer agents for the present invention. Suitable cobalt chelates are known in the art and described in WO98 / 04603. A particularly suitable compound is bis(borondifluorodimethylglyoximate)cobaltate(II), also known as CoBF. Catalytic chain transfer agents are generally very effective at low concentrations, and therefore can be used at relatively low concentrations, e.g., <0.5 wt%, preferably <0.1 wt% (based on monofunctional monomer), compared to conventional thiol chain transfer agents. Surprisingly, we have found that catalytic chain transfer compounds based on cobalt complexes can be used very effectively in the polymerization process of the invention to obtain soluble branched polymers at concentrations of less than 0.05% by weight (500 ppmw), for example 0.0001-0.01% by weight (1-100 ppmw), based on the monofunctional monomer.
[0030] The amount of chain transfer agent is at least 0.1 or 0.5 or 1 weight percent based on the total weight of the reactants. According to some embodiments, the amount of chain transfer agent is no more than 10 or 8 or 6 or 5 weight percent based on the total weight of the reactants.
[0031] The reactants further comprise a crosslinking agent. The inclusion of the crosslinking agent results in branching. However, the amount of crosslinking agent must be controlled so that the polymer does not crosslink. According to an embodiment, the amount of crosslinking agent is equal to or less than the amount of chain transfer agent. According to an embodiment, the amount of crosslinking agent is less than the amount of chain transfer agent. According to an embodiment, the weight percentage of the crosslinking agent is lower than the weight percentage of the chain transfer agent. According to an embodiment, the weight ratio of the chain transfer agent to the crosslinking agent is in the range of 1:1 or 1.5:1 to 10:1. According to an embodiment, the molar percentage of the crosslinking agent is lower than the molar percentage of the chain transfer agent. According to an embodiment, the molar ratio of the chain transfer agent to the crosslinking agent is at least 1.2:1 or 1.4:1 or 1.5:1 or 1.7:1 or 2:1 or 4:1. According to an embodiment, the molar ratio of the chain transfer agent to the crosslinking agent is less than 20:1 or 15:1 or 10:1.
[0032] The crosslinker can be any polyfunctional unsaturated monomer - i.e., any monomer with two or more unsaturated groups available for addition polymerization. Examples of suitable difunctional monomers include ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, allyl (meth)acrylate, divinylbenzene, and derivatives thereof. Examples of trifunctional include tripropylene glycol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate. Tetrafunctional monomers such as pentaerythritol tetra(meth)acrylate and hexafunctional monomers such as dipentaerythritol hexa(meth)acrylate can also be used. Optionally, the multifunctional monomer may comprise a mixture of two or more multifunctional compounds. According to one embodiment, the crosslinking agent is [ka] It is.
[0033] The amount of crosslinker according to some embodiments is at least 0.1 or 0.5 or 1 weight percent based on the total weight of the reactants. According to some embodiments, the amount of crosslinker is no more than 10 or 8 or 6 or 5 weight percent based on the total weight of the reactants.
[0034] According to certain embodiments, the crosslinker is BGDMA and the chain transfer agent is BMA. According to certain embodiments, the acrylate monomer (e.g., methyl methacrylate) is present in an amount of 90 to 99 weight percent, the amount of BGDMA ranges from 1 or 2 to 4 or 3 weight percent, and the amount of BMA ranges from 1 or 2 or 3 to 7 or 6 weight percent, based on the total weight of the acrylate monomer, BGDMA, and BMA.
[0035] The branched polymers can be made using any free radical polymerization technique, for example, solution, suspension, emulsion, and bulk polymerization techniques can all be used, for example, conventional emulsion polymerization can be used.
[0036] Surfactants or emulsifiers can be used. Examples of emulsifiers include nonionic, anionic, and cationic emulsifiers.
[0037] Suitable nonionic emulsifiers are araliphatic or aliphatic nonionic emulsifiers, examples of which include ethoxylated mono-, di-, and trialkylphenols (degree of ethoxylation: 3 to 50, alkyl radical: C4-C 10 ), ethoxylates of long-chain alcohols (ethoxylation degree: 3-100, alkyl radical: C8-C 36), as well as polyethylene oxide / polypropylene oxide homopolymers and copolymers. These may contain alkylene oxide units in random distribution or copolymerized in the form of blocks. For example, ethylene oxide / propylene oxide block copolymers are very suitable. Ethoxylates of long-chain alkanols (alkyl radicals C1-C 30 It is preferable to use linear C 12 -C 20 Those having alkyl radicals and an average degree of ethoxylation of 10 to 50, as well as ethoxylated monoalkylphenols, are also particularly preferred.
[0038] Suitable anionic emulsifiers are, for example, alkyl sulfates (alkyl radical: C8-C 22 ), ethoxylated alkanol (ethoxylation degree: 2-50, alkyl radical: C 12 -C 18 ) and ethoxylated alkylphenols (ethoxylation degree: 3-50, alkyl radical: C4-C9), sulfuric acid monoesters, alkylsulfonic acids (alkyl radical: C 12 -C 18 ), and alkylarylsulfonic acids (alkyl radical: C9-C 18 Further suitable emulsifiers are described in Houben-Weyl, Methoden der organischen Chemie, volume XIV / 1, Makromolekulare Stoffe, Georg-Thieme-Verlag, Stuttgart, 1961, pp. 192-208. Also suitable as anionic emulsifiers are bis(phenylsulfonic acid) ethers and phenylsulfonic acid ethers having C4-C in one or both aromatic rings. 24 These compounds, for example from US Patent No. 4,269,749, are well known and commercially available, for example in the form of Dowfax™ 2A1 (Dow Chemical Company).
[0039] Suitable cationic emulsifiers are preferably quaternary ammonium halides, such as trimethylcetylammonium chloride, methyltrioctylammonium chloride, benzyltriethylammonium chloride, or N-C6-C 20 -alkylpyridine, -morpholine or -imidazole quaternary compounds, for example N-laurylpyridinium chloride.
[0040] The amount of emulsifier (or surfactant) can be at least 0.01 or 0.1 weight percent to 10 or 5 weight percent based on the amount of monomer being polymerized.
[0041] An initiator can be used. Examples of initiators can be initiated by any suitable method of generating free radicals, such as by thermally induced decomposition of thermal initiators such as azo compounds, peroxides, or peroxyesters. Thus, the polymerization mixture also preferably contains a polymerization initiator, which can be any of those known and conventionally used in free radical polymerization reactions. Examples of azo initiators include azobis(isobutyronitrile) (AIBN), azobis(2-methylbutyronitrile), azobis(2,4-dimethylvaleronitrile), and azobis(4-cyanovaleric acid). Examples of peroxide and peroxy initiators include hydrogen peroxide, sodium peroxide, potassium peroxide, t-butyl hydroperoxide, cumene hydroperoxide, dilauroyl peroxide, tert-butyl peroxyneodecanoate, dibenzoyl peroxide, cumyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethyl acetate, and tert-butyl peroxybenzoate. Examples of additional initiators include ammonium and / or alkali metal persulfates, sodium perborate, perphosphoric acid and its salts, potassium permanganate, and ammonium or alkali metal salts of peroxydisulfate, such as alkali metal or ammonium peroxydisulfates, diacetyl peroxide, dibenzoyl peroxide, succinyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl perpivalate, tort-butyl peroxy-2-ethylhexanoate, te rt-butyl permaleinate, cumene hydroperoxide, diisopropyl peroxydicarbamate, bis(o-toluoyl) peroxide, didecanoyl peroxide, dioctanoyl peroxide, dilauroyl peroxide, tert-butyl perisobutyrate, tert-butyl peracetate, di-tert-amyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, 2,2'-azobis(2-amidino-propane) dihydrochloride, or 2,2'-azobis(2-methylbutyronitrile).Mixtures of these initiators are also suitable. It is also possible to use reduction / oxidation (i.e. redox) initiator systems as initiators. Redox initiator systems consist of at least one, usually inorganic, reducing agent and one organic or inorganic oxidizing agent. The oxidizing component includes, for example, the emulsion polymerization initiators already specified above. The reducing component includes, for example, alkali metal salts of sulfite, such as sodium sulfite, sodium hydrogen sulfite, alkali metal salts of disulfite, such as sodium disulfite, hydrogen sulfite adducts of aliphatic aldehydes and ketones, such as acetone sulfite, or reducing agents, such as hydroxymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems can be used with soluble metal compounds whose metal components can exist in multiple valence states. Typical redox initiator systems are, for example, ascorbic acid / iron(II) sulfate / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium disulfite, tert-butyl hydroperoxide / Na hydroxymethanesulfinate. Individual components, such as the reducing component, can also be mixtures, an example being a mixture of the sodium salt of hydroxymethanesulfinic acid and sodium disulfite.
[0042] The amount of initiator is generally at least 0.01 or 0.05 or 0.01 weight percent to 10 or 5 or 3 weight percent based on all monomers being polymerized.
[0043] The branched polymer is not crosslinked. For example, this can be demonstrated by evaluating the solubility of the polymer in a solvent such as tetrahydrofuran. Crosslinked polymers are not soluble.
[0044] Branched polymers according to certain embodiments may be characterized by a polymer branching ratio g' of less than 1, 0.95, 0.9, 0.8. According to some embodiments, g' is at least 0.5 or 0.6 or 0.7. The polymer branching ratio (g') is measured at each elution volume increment in gel permeation chromatography (GPC) analysis. Intrinsic viscosity of branched polymer ([η]分岐 ) of the same molecular weight (M) Intrinsic viscosity of linear polymer ([η] 直鎖状 ) (Equation 1). For linear polymers, the g' value is equal to 1, for branched polymers, g' is less than 1.
number
[0045] Molecular weight analysis: absolute molecular weight of polymer (M w , M n ), PMMA relative molecular weight (M w_PMMA , M n_PMMA ), intrinsic viscosity ([η] w , [η] n ), and branching ratio (g') can be measured by gel permeation chromatography with an online multi-angle light scattering (MALS) detector, a viscometer (VS), and a differential refractive index (dRI) detector. For example, a GPC instrument setup can include an Agilent 1200 series HPLC system (degasser, pump, autosampler, column oven), a Wyatt HELEOS II MALS detector, a Wyatt ViscoStar II viscometer, and a Wyatt T-rEX dRI detector. Polymer separation can be performed, for example, with a column set with two PLgel mixed-B LS columns (particle size 10 μm, length 7.5x300 mm) using tetrahydrofuran (THF) as the mobile phase at a flow rate of 1 mL / min. The column oven temperature can be set at 30 °C. oThe column is set at 0.5°C. A set of 10-point PMMA standards (Agilent EasiCal PM-1) is used to calibrate the GPC column and obtain PMMA relative molecular weights. Absolute molecular weights are obtained from MALS detection using the Zimm format, and intrinsic viscosity data are obtained from the viscometer. The high molecular weight fraction data (PMMA relative molecular weights above 6500 Da) are used to calculate the average g' values. To keep the g' calculations consistent, a linear PMMA model from the Mark-Houwink equation (Eq. 2, where K = 0.0383 mL / g and α = 0.581 for the non-BA-containing samples in Table 2, and K = 0.03044 mL / g and α = 0.615 for the BA-containing polymers in Table 2) is used to calculate the average g' value using the M data from the MALS detection ([η] in Eq. 1). 直鎖状 ) is obtained.
number
[0046] The weight average molecular weight M of the branched polymer measured by GPC w According to certain embodiments, the weight average molecular weight is at least in the range of 8000 or 10,000 or 15,000 or 20,000 g / mol. According to certain embodiments, the weight average molecular weight is not more than 100,000 or 80,000 g / mol. According to certain embodiments, the number average molecular weight M of the branched polymer, as measured by GPC, is n is at least 3000 or 4000 or 5000 g / mol. According to certain embodiments, the number average molecular weight is not more than 50,000 or 40,000 or 30,000 or 20,000 g / mol.
[0047] According to one particular embodiment, the branched structure is a dendritic structure.
[0048] According to certain embodiments, the amount of branched polymer in the composition is at least 1 or 3 or 5 or 10 percent by weight. The composition can be in a concentrated form and then mixed with a soft acrylic resin polymer to obtain the desired amount of branched polymer in the composition to be processed (e.g., extruded, injection molded). In concentrated form, the amount of branched polymer can constitute a significant portion of the composition, for example, up to 60 or 50 or 40 percent by weight. To obtain the advantage of a higher melt flow index (lower viscosity) for use in processing, the composition can include an amount of branched polymer up to 30 or 25 or 20 percent by weight, according to certain embodiments. The branched polymer is soluble (miscible) in the soft acrylic resin in the amount used such that the composition is shown to be transparent.
[0049] The composition may further include additional additives desired in the final product. Examples of such additives include UV light stabilizers and antioxidants. According to certain embodiments, the additives are selected so that the composition remains transparent. Examples of UV light stabilizers include benzophenones, benzotriazoles, triazines, benzoxazinones, hindered amine light stabilizers (HALS), and hindered benzoates. Commercially available UV and light stabilizers include Cyasorb light absorbers and light stabilizers from Solvay, Cyasorb Cynergy Solutions, TINUVIN FROM BASF, LowLite from Chemtura, OnCap from PolyOne, and Light Stabilizer from EI du Pont de Nemours and Company of Delaware, USA.210. Examples of antioxidants include phenolic antioxidants and combinations of phenolic antioxidants with phosphites, thioethers, or organic sulfides. Phenolic antioxidants include fully hindered and partially hindered phenols; and sterically hindered amines such as tetramethyl-piperidine derivatives. Suitable phenolic antioxidants include vitamin E, and IRGANOX™ 1010 from BASF. IRGANOX™ 1010 includes pentaerythritol tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate). Additional examples of antioxidants include acetylcysteine, arbutin, ascorbic acid, ascorbic acid polypeptide, ascorbyl dipalmitate, methylsilanol ascorbyl pectate, ascorbyl palmitate, ascorbyl stearate, BHA, p-hydroxyanisole, BHT, t-butylhydroquinone, caffeic acid, camellia oil, chitosan ascorbate, chitosan glycolate, chitosan salicylate, chlorogenic acid, cysteine, cysteine HCI, decylmercaptomethylimidazole, erythorbic acid, diamylhydroquinone, di-t-butylhydroquinone, dicetyl thiodipropionate, dicyclopentadiene / t-butylcresol copolymer. Polymer, digalloyl trioleate, dilauryl thiodipropionate, dimyristyl thiodipropionate, dioleyl tocopheryl methylsilanol, isoquercitrin, diosmin, disodium ascorbyl sulfate, disodium rutinyl disulfate, distearyl thiodipropionate, ditridecyl thiodipropionate, dodecyl gallate, ethyl ferulate, ferulic acid, hydroquinone, hydroxylamine HCI, hydroxylamine sulfate, isooctyl thioglycolate, kojic acid, madecassoside, magnesium ascorbate, magnesium ascorbyl phosphate, melatonin, methoxy-PEG-7 rutinyl succinatesuccinate), methylenedi-t-butylcresol, methylsilanol ascorbate, nordihydroguaiaretic acid, octyl gallate, phenylthioglycolic acid, phloroglucinol, potassium ascorbyl tocopheryl phosphate, thiodiglycolamide, potassium sulfite, propyl gallate, rosmarinic acid, rutin, sodium ascorbate, sodium ascorbyl / cholesteryl phosphate, sodium bisulfite, sodium erythorbate, sodium metadisulfide, sodium sulfite, sodium thioglycolate, sorbityl furfural, tea tree (melaleuca alternifolia) oil, Tocopheryl acetate, tetrahexyldecyl ascorbate, tetrahydrodiferuloylmethane, tocopheryl linoleate / oleate, thiodiglycol, tocopheryl succinate, thiodiglycolic acid, thioglycolic acid, thiolactic acid, thiosalicylic acid, thiotaurine, retinol, tocopheryl acetate, tocopheryl acetate 10, tocopheryl acetate 12, tocopheryl acetate 18, tocopheryl acetate 50, tocopherol, tocophersolan, tocopheryl linoleate, tocopheryl acetate nicotinate, tocoquinone, o-tolylbiguanide, tris(nonylphenyl)phosphite, ubiquinone, zinc dibutyldithiocarbamate, and mixtures thereof. According to certain embodiments, the total amount of additives (if any) used is less than 10 or 5 or 3% by weight based on the total weight of the composition.
[0050] The compositions are characterized by a melt flow index of at least 30, 40, 50, or 60 g / 10 min, 220° C., 10 kg according to ASTM D 1238. According to certain embodiments, the melt flow index is less than 100 or 90 g / 10 min, 220° C., 10 kg.
[0051] According to certain embodiments, the composition is not turbid, e.g., the turbidity, as measured by light transmission, is less than 1% when measured according to ASTM D1003 using a suitable device, e.g., BYK HazeGuard Plus.
[0052] The composition can be made by blending the components. According to one embodiment, the components can be cold blended (e.g., mixing two aqueous latexes) and then lyophilized or solidified. According to another embodiment, the components can be mixed in powder form.
[0053] The compositions have favorable melt flow indices making them useful for extrusion, calendaring, and injection molding applications.
[0054] According to some embodiments, the composition is extruded as a thin film. The film may have a thickness of 150 or 125 or 100 microns or less. According to some particular embodiments, the thickness is at least 50 microns. According to some embodiments, the composition is coextruded as a layer of a multi-layer film. The layer may have a thickness of 150 or 125 or 100 microns or less. According to some particular embodiments, the layer has a thickness of at least 10, 20, 30, or 50 microns. The film is transparent. The film does not exhibit flute whitening. EXAMPLES
[0055] Example 1 - Synthesis of branched polymer additive The emulsion polymerization is carried out in a 5 liter, 4-neck round bottom flask equipped with a mechanical stirrer, heating mantle, thermometer, temperature controller, and N2 inlet. The reactor is charged with 1063 parts deionized water, 6.01 parts A18 alkyl sulfate surfactant (42% in water), and 0.091 parts Fe-EDTA complex (as Sequestrene). The reactor contents are heated to 75°C with an N2 sweep. The monomer emulsion is made up of 238.5 parts deionized water, 24.04 parts A18 alkyl sulfate surfactant (42% in water), 50 parts butyl acrylate (BA), 875 parts methyl methacrylate (MMA), 50 parts butyl 3-mercaptopropionate (BPA), 10 parts methyl methacrylate (MMA), 1 ... Nate(BMP), and 25 parts of 1,4 butanediol dimethacrylate (BGDMA). Mechanical agitation is applied to effect emulsification. The redox initiator system consists of two separate solutions. The first is a 2% (by weight) solution of t-butyl hydroperoxide (t-BHP) in water (oxidizer) and the second is a 2% (by weight) solution of sodium formaldehyde sulfoxiate (SFS) in water (reducer), both totaling 80 parts. 94.69 parts of the monomer emulsion are added to the reactor and one minute later (time zero), simultaneous feeds of the t-BHP and SFS solutions are started at 0.89 parts / min (both 90 min feed time). The reactor temperature is maintained at 75°C throughout the polymerization process. After 15 minutes, the remaining monomer emulsion is fed at 19.46 parts / min (60 min feed time). At the end of the monomer feed (total reaction time from time zero 75 minutes), t-BHP and SFS continued for an additional 15 minutes (total reaction time from time zero 90 minutes). The reaction is then cooled to 40° C. and filtered through cheesecloth. The emulsion particle size of the polymer made in this manner was determined to be 124 nm (by light scattering), the solids content was 39.9% (by gravimetry), and the residual BA and MMA monomers were 27 and 98 ppm, respectively (by headspace gas chromatography). A portion of the latex is then freeze-dried to a powder using dry ice and then a vacuum oven.
[0056] Example 2 - Cold Blend Paraloid™ 21308XP multi-stage flexible acrylic resin (FAR) was used to make cold blends (i.e., additives in aqueous solution mixed with aqueous solutions of multi-stage flexible acrylic resin) of various additive polymers. The relative amounts of methyl methacrylate monomer, chain transfer agent (BMP), and crosslinker (BGDMA) are shown in Table 1. Rolled films of 250 microns thickness were made. Samples were tested for turbidity, fluting whitening, and melt flow index as described above. Additionally, the molecular weights by GPC-MALS, GPC-VS, and CC-PMMA as described above for the additives used in the blends listed in Table 1 are shown in Table 2. [Table 1] [Table 2]
[0057] Example 3 - Powder Blend Powders of the additives were made and then freeze-dried and blended with a powder of Paraloid™ 21308XP. Rolled films were made at 185° C. using a laboratory two-roll mill (Collin GmbH, Gewerbestrasse, Germany). The compositions are as shown in Table 3. The films were tested for turbidity and fluting whitening, and the resins were tested for MFI as above. None of the samples showed turbidity greater than 2%. [Table 3]
[0058] Example 4 - Film Extrusion Compositions containing Paraloid™ 21308XP from The Dow Chemical Company and the additives listed in Table 4 (additive loading of 15%) were extruded through a T ("coat hanger") die. The results are shown in Table 4, which shows film thickness and / or quality in mils for varying extruder RPM (15 or 20) and extrusion speed in feet / min (e.g., 5.0, 4.5, 4.0, 3.0). MFI is g / 10 min, 220° C., 10 kg. [Table 4]
[0059] Example 5 - Spiral Flow Samples of Paraloid 21308XP with and without additive A6 loaded at 15 weight percent additive were tested for spiral flow results using an AUBURG injection molding machine (Arthur-Hehl-Straße, Germany). As shown in Table 5, inventive Example 5 showed better (longer) flow distance and could be processed over a wider temperature range. [Table 5]
[0060] Example 6 Compositions containing Paraloid™ 21308XP from The Dow Chemical Company and the additives listed in Table 6 (additive loading of 15 weight percent) were extruded through a T ("coat hanger") die at various RPM (15 or 20) and extrusion speeds (e.g., 5.0, 4.5, 4.0) in feet per minute. The MFI is g / 10 min, 220° C., 10 kg. The resulting film thicknesses are shown in Table 6, and the film tensile properties measured according to ASTM D882 (speed 5 in / min) are shown in Table 7. As shown, the linear additive caused surging at speeds of 5 (ft / min) and 4.5 (ft / min), but the tensile properties are superior with the branched additive. [Table 6] [Table 7]
[0061] Example 7 Additive powders were made, freeze-dried, and blended with PVC (clear PVC masterbatch formulation) and Paraloid™ 21308XP powders, or pellet PMMA (Plexiglas 7H) and Paraloid™ 21308XP. The blended resins were processed into thin films using a laboratory two-roll mill. The compositions are as shown in Table 8. The films were tested for light transmittance (TT%) and turbidity (H%). TT means total transmittance measured by BYK HazeGuard Plus. H means turbidity (light scattering) measured by BYK HazeGuard Plus), both according to ASTM D1003. [Table 8]
Claims
1. 1. A composition comprising: Multi-stage soft acrylic resin, a branched polymer that is the reaction product of a mixture comprising one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1 to 10 weight percent, and a crosslinking agent in an amount of 0.1 to 10 weight percent, the weight percent being based on the total amount of said mixture, with the proviso that the amount of said crosslinking agent in moles is less than the amount of said chain transfer agent in moles; the composition comprises 75 to 95 weight percent of the multi-stage soft acrylic resin and 5 to 25 weight percent of the branched polymer, based on the total weight of the composition; The weight average molecular weight M of the branched polymer measured by GPC w is in the range of 8,000 to 80,000 g / mol; The multi-stage soft acrylic resin is (i) a first core stage, the first core stage being a reaction product of one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates, and one or more crosslinking monomers, graft linking monomers, or combinations thereof, wherein the amount of units derived from the alkyl acrylates and / or alkyl methacrylates ranges from 95 to 99.9 weight percent of the first core stage, the amount of units derived from the crosslinking monomers and / or graft linking monomers ranges from 0.1 to 5 weight percent of the first core stage, and the first core stage is crosslinked with a Tg in the range of -85 to -10°C; (ii) one or more intermediate stage layers, each of said intermediate stage layers comprising 93 to 100 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates, 0 to 5 weight percent of units derived from a crosslinking monomer, a graft linking monomer, or a combination thereof, and optionally 0 to 2.0 weight percent of units derived from one or more chain transfer agents, with a compositional gradient between said intermediate stage layers such that the Tg transitions over the width of the intermediate region in a subrange from −30° C. to 70° C.; (iii) an outermost layer comprising 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, and styrenic monomers, and combinations thereof, and 0 to 1.5 weight percent units derived from one or more chain transfer agents, the outermost layer having a Tg of 40° C. to 110° C.; A composition comprising:
2. The composition of claim 1 , wherein the branched polymer is not crosslinked.
3. 3. The composition of claim 1 or 2, wherein the one or more monoethylenically unsaturated ester monomers have the structure R'-C(O)O-R, where R is a hydrocarbyl group of 1 to 12 carbon atoms and R' is a monoethylenically unsaturated aliphatic group having at least 2 or 3 carbon atoms.
4. The chain transfer agent may be selected from the group consisting of propyl mercaptan, butyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecyl mercaptan, thioglycolic acid, mercaptopropionic acid, alkyl thioglycolate, mercaptoethanol, mercaptoundecanoic acid, thiolactic acid, thiobutyric acid, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetrathioglycolate, penta The composition of any one of claims 1 to 3, wherein the mercaptopropyl ether is selected from the group consisting of erythritol tetrathiolactate, pentaerythritol tetrathiobutyrate, dipentaerythritol hexa(3-mercaptopropionate), dipentaerythritol hexathioglycolate, tripentaerythritol octa(3-mercaptopropionate), tripentaerythritol octathioglycolate, butyl 3-mercaptopropionate, and combinations of two or more thereof.
5. The composition of any one of claims 1 to 4, wherein the crosslinking agent is selected from the group consisting of ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, allyl (meth)acrylate, divinylbenzene and its derivatives, tripropylene glycol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and combinations of two or more thereof.
6. The composition of any of claims 1 to 5, wherein the amount of the crosslinker is from 0.5 to 4 weight percent.
7. The composition of any of claims 1 to 6, wherein the amount of the chain transfer agent is from 1 to 5 weight percent.
8. The composition of any of claims 1 to 7, wherein the branched polymer is characterized by a g' of 0.9 or less.
9. The composition according to any one of claims 1 to 8, having a melt flow index of at least 40 g / 10 min, 220°C, 10 kg.
10. The composition of any of claims 1 to 9, further comprising a polymer selected from acrylate polymers, polyesters, polycarbonates, polyamides, and halogenated polyolefins having at least 20 weight percent halogen.
11. An extruded film comprising a layer of the composition of any one of claims 1 to 10.
12. 12. The film of claim 11 having a thickness of 150 microns or less.
13. 13. The film of claim 11 or 12, which is transparent and does not exhibit crease whitening.
Citation Information
Patent Citations
Methyl methacrylate-based resin composition and its molded product
JP1998259287A
Injection molded product of methyl methacrylate-based resin
JP1999158344A
Multi-Stage Polymer Composition and Films Made Therefrom
US20150183944A1